Organic Ligands in Marine Trace Metal Biogeochemistry - Kristen N. Buck (Frontiers Research Topics, 2018)
This research topic highlights the most recent accomplishments of a Scientific Committee on Oceanic Research (SCOR) Working Group, SCOR WG 139: Organic Ligands - A Key Control on Trace Metal Biogeochemistry in the Ocean.